(untitled) (The International Journal for Scientific Research, 2025)
This study examined the importance of feasibility studies in driving the success of economic institutions in Amman, Jordan, using a descriptive-analytical approach. The research sample consisted of 385 randomly selected owners of economic institutions in the city. A validated and reliable questionnaire was utilized for data collection, and SPSS was employed for analysis. Findings demonstrated that feasibility studies have a statistically significant impact on the success of economic institutions. Key aspects such as preliminary analysis, market analysis, financial analysis, and technical analysis were highlighted as crucial contributors. The study recommended forming specialized teams to conduct detailed preliminary analyses to establish a clear strategic vision. It also stressed the importance of implementing ongoing market analysis systems to monitor customer trends and adapt to emerging opportunities effectively.